The Food for Feed Concept: Redefining the Use of Hotel Food Residues in Broiler Diets - Giamouri, Elisavet; Pappas, Athanasios C.; Papadomichelakis, George; Simitzis, Panagiotis E.; Manios, Thrassyvoulos; Zentek, Juergen; Lasaridi, Katia; Tsiplakou, Eleni; Zervas, George (Sustainability, 2022)
The large quantities of food waste that are generated every year have raised management concerns. Animal diets might be a feasible strategy for utilizing food waste and partially replacing commercially available feedstuffs. The present study examined the potential use of food waste originating from hotels for broiler chickens’ diets. Two hundred and forty (240) one-day-old broilers were allocated into four treatment groups, namely, control (C), non-meat treatment (NM), non-sterilized treatment (NS) and sterilized treatment (S), each with 5 replicate pens of 12 broilers. The experimental period lasted 42 days. Several parameters were recorded throughout the experiment, such as the initial and final body weight, the feed conversion ratio (FCR), the traits, some biochemical and hematological parameters, the weight of internal organs and selected breast meat quality indices. The results showed no major differences in health parameters and the carcass quality traits. There was also no difference in growth rate between the three groups (C, NS, S), but broilers fed the NM diet (without meat remnants) had a significantly lower growth rate by 11.4% compared to the control. Food waste residues can be an alternative feedstuff for broiler chickens and can maintain performance at acceptable levels.